Traditional â€œCongklakâ€ Games and Cooperative Character in Mathematics Larning - Kamid Kamid; Syaiful Syaiful; Roseli Theis; Sufri Sufri; Sabila Eka Septi; Rido Ilham Widodo (Universitas Pendidikan Ganesha, 2021)
Mathematics is one material that most students do not like. In addition to being less attractive, elementary school students also tend to have grades among their peers. This shows the lack of attention applied in learning mathematics. This study aimed to analyze the relationship and influence of cooperative characters with student responses by using traditional games in learning. This type of research uses quantitative methods with the type of comparative research. This research was conducted by distributing questionnaires. The data analysis technique used is random sampling. The research subjects in this study were 120 students. The results obtained are that the cooperative character in the traditional game of Congklak is superior, which is in a very good percentage (60%). The student's response to the traditional game of congklak was very good (55%). The results of the correlation test of the cooperative character of students in traditional games, namely, there is a relationship between the character of cooperation with students' responses to the traditional game of congklak in mathematics. It can be said that there is a relationship and influence of the character of cooperation with student responses. The implication of this research is that playing traditional games in learning can increase students' interest in learning mathematics.